Meningkatkan Keterampilan Menyimak melalui Listening Log - Athena, Tera; Ulfa, Siti Maria; Kiptiyah, Mariyatul; Hafidz, Moh.; Wijaya, Moh. Kurdi (Journal of Smart Community Service, 2025)
This community service program aims to improve listening skills by implementing the Autonomous learning strategy through the Listening Log. This service was carried out from January to February 2025 at SMKN 1 Bangkalan. Autonomous learning is the ability of learners to gain knowledge and skills through a process that they determine themselves. This learning process can be seen from filling out the Listening Log as a form of independent report for each student when using their time to study outside of class hours. The results of this community service can be seen from the results of the questionnaire that students feel that the use of the listening log is very useful because they can correct their own progress and effotrs through the agendas that they fill in or complete. They feel comfortable being given the freedom to get sources of material that suit their preferences so that they can practice theit listening skills. In this way, students independently manage their time when they are not in the classroom. By themselves they are better able to find their way of learning, especially in listening skills.